Molecular Identification of Two DNA Methyltransferase Genes and Their Functional Characterization in the Anti-Bacterial Immunity of Antheraea pernyi - Kausar, Saima; Abbas, Muhammad Nadeem; Gul, Isma; Liu, Ruochen; Li, Qianqian; Zhao, Erhu; Lv, Muhan; Cui, Hongjuan (Frontiers in Immunology, 2022)
Under different physiological conditions, such as microbial infection, epigenetic mechanisms regulate genes at the transcription level in living organisms. DNA methylation is a type of epigenetic mechanism in which DNA methyltransferases modify the expression of target genes. Here, we identified a full-length sequence of DNMT-1 and DNMT-2 from the Chinese oak silkworm, A. pernyi, which was highly similar to the homologous sequences of Bombyx mori. ApDNMT-1 and ApDNMT-2 have unique domain architectures of insect DNMTs, highlighting their conserved functions in A. pernyi. ApDNMT-1 and ApDNMT-2 were found to be widely expressed in various tissues, with the highest levels of expression in hemocytes, the ovary, testis, and fat bodies. To understand the biological role of these genes in microbial resistance, we challenged the fifth instar larvae of A. pernyi by administrating Gram-positive and Gram-negative bacteria and fungi. The results revealed that transcript levels of ApDNMT-1 and ApDNMT-2 were increased compared to the control group. The inhibition of these genes by a DNMTs inhibitor [5-azacytidine (5-AZA)] significantly reduced bacterial replication and larvae mortality. In addition, 5-AZA treatment modified the expression patterns of antimicrobial peptides (AMPs) in the A. pernyi larvae. Our results suggest that ApDNMT-1 and ApDNMT-2 seem to have a crucial role in innate immunity, mediating antimicrobial peptide responses against bacterial infection in A. pernyi.